A universal child grant in Brazil: What must we do, and what can we expect from it? - Sergei Soares; Graziela Ansiliero; Aline Diniz Amaral; Pedro H. G. Ferreira de Souza; Luis Henrique Paiva (International Policy Centre for Inclusive Growth (IPC-IG), 2019)
The objective of this paper is to propose a universal child grant for Brazil. We will discuss the rationality behind the proposal, how best to design it, its initial operational set-up,its costs, and some of its distributive aspects. The proposed allowance is based on the unification of the three child allowances that currently exist in the country.
Keywords: 330; Universal; child; grant; Brazil; expect